Model 3D Sebaran Akuifer Di Geowisata Danau Dendam Tak Sudah Kota Bengkulu Menggunakan Metode Vertical Electrical Sounding (3d Model of Aquifer Layer Distribution Around Lake Dendam Nature Park Of Bengkulu City Using Schlumberger Configuration Geoelectric Method) - Intan Gayatriani; Suhendra; Refrizon; Halauddin; Usman Gumanty; Sendiya Verentina; Marven Saputra (Asosiasi Peneliti dan Teknisi Kehutanan dan Lingkungan Hidup Indonesia (APTKLHI), 2025)
The city of Bengkulu is the capital of Bengkulu Province, has a lake called Danau Dendam Tak Sudah (DDTS), which is located in a strategic area due to its potential underground water resources. The purpose of this study was to determine the distribution of aquifers around DDTS, in Surabaya Village, Sungai Serut Subdistrict, Bengkulu City through the geophysical method of Vertical Electrical Sounding (VES) with Schlumberger Configuration. VES measurement points were taken at 21 points. This study was conducted in a residential area to determine whether the subsurface aquifer is connected to water in DDTS. Data acquisition used the MAE X612-EM VHR Multi-Channel Resistivitimeter Geoelectric tool. The results of data acquisition in the field were then processed using Progress, Strater, IP2win and Surfer software. The interpretation results show that the resistivity value, depth and thickness vary as well as the existence of 2 - 5 layers as the geological structure and characteristics of the local lithology with a resistivity value of 2 - 19 Ω.m is groundwater, resistivity value of 19 - 30 Ω.m clay flake, resistivity value of 30 - 70 Ω.m clay, resistivity value of 70 - 100 Ω.m top soil and resistivity value of 100 - 150 Ω.m sandy gravel. Shallow aquifers are estimated to be at a depth of < 20 m, while the deep aquifers are located at > 25 m below the surface and have a thickness of 2 to 78.5 m.